First Case Report of Prader–Willi-Like Syndrome in Colombia - Candelo, Estephania; Feinstein, Max M.; Ramirez-Montaño, Diana; Gomez, Juan F.; Pachajoa, Harry (Frontiers in Genetics, 2018)
Background: Prader–Willi-like syndrome (PWLS) is believed to be caused by a variety of disruptions in genetic pathways both inside and outside of the genetic region implicated in PWS. By definition, PWLS does not demonstrate mutations in the 15q11–q13 region itself. It is a rare disorder whose clinical hallmarks include hypotonia, obesity, short extremities and delayed development. This syndrome has been described in patients with 1p, 2p, 3p, 6q and 9q chromosome abnormalities and in cases with maternal uniparental disomy of chromosome 14 and fragile X syndrome. Case presentation: In the present report, we describe a 9-year-old Colombian patient who demonstrated features of PWS and was ultimately diagnosed with PWLS after genetic analysis revealed a 14.97 Mb deletion of 6q16.1–q21. Conclusions: This is the first reported case of PWLS in Colombia and represents one of the largest documented 6q21 deletions. Keywords: Prader–Willi-like syndrome, Prader–Willi-like phenotype, Prader–Willi syndrome (PWS), 6q16.1–q21 deletion, Pediatric Obesity